Res Judicata In The Malaysian Syariah Court With Special Reference To The Case Of S Osman Bin S Karim & Another V Ak Othman Shah Bin Pg Mohd Yussof & Another: Case Note - Yaakob, Noor Inayah (Journal of Malaysian and Comparative Law, 1999)
Res judicata is a fundamental doctrine of all courts that there must be an end of litigation.